2017
DOI: 10.7752/jpes.2017.04283
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:Problem: executive functions refer to the subject's ability to engage in goal-oriented behavior, performing voluntary, independent, self-organized and goal-directed actions, indeed, the general physical training, and the sports can enhance this functions, studys to determinate the effect of martial arts upon the executive functions in childrens are rare. Objective: to identify if the Karatekas has best executive functions that non karatekas. Methods: 66 volunteers were selected, including 36 male kara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…26 Moreover, positive results on resilience, self-efficacy, selective attention, and problem solving have also been reported after school-based karate interventions among children and adolescents. 8,9 These findings overall support the beneficial effects of including martial art-related activities-and particularly karateduring physical education lessons. It is worth noting, however, that the present results suggest that the proportion of children who actually obtain meaningful benefits from the intervention would be lower than previously expected, at least for SDQ scores (responsiveness rate of 17%).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…26 Moreover, positive results on resilience, self-efficacy, selective attention, and problem solving have also been reported after school-based karate interventions among children and adolescents. 8,9 These findings overall support the beneficial effects of including martial art-related activities-and particularly karateduring physical education lessons. It is worth noting, however, that the present results suggest that the proportion of children who actually obtain meaningful benefits from the intervention would be lower than previously expected, at least for SDQ scores (responsiveness rate of 17%).…”
Section: Discussionmentioning
confidence: 54%
“…In this regard, growing evidence suggests that participating in martial arts could be particularly beneficial. [5][6][7][8][9] For instance, Lakes and Hoyt reported positive effects of a 3-month school-based martial arts intervention on cognitive and affective self-regulation, prosocial behavior, classroom's conduct, and maths performance in children. 7 However, although preliminary evidence supports the beneficial effects of karate on psychosocial functioning and academic performance, 8,10,11 there is a lack of large randomized controlled trials (RCT).…”
Section: Introductionmentioning
confidence: 99%
“…Study participants didn't have Kata practice in their usual karate training routine. Even though evidence shows that any resistance training and bimanual coordination in karate require attention, work memory, and discipline (Lima et al, 2017), skipping Kata means missing opportunity to improve. There are lack of studies and opinions on what could substitute Kata for children, to gain the same positive effects but in a more understandable and acceptable way for children from western societies.…”
Section: Discussionmentioning
confidence: 99%
“…Martial arts also improve resilience in children (Moore et al, 2021). One of the techniques that is aimed specifically to improve self-control and self-awareness is Kata, because it provides inhibitory control and demands mindfulness (Lima et al, 2017). Hence body awareness has a positive correlation with performance emotional state in athletes (Erden & Emirzeoglu, 2018).…”
Section: Self-esteem and Body Awareness Among Children Practicing Karatementioning
confidence: 99%
“…Preliminary evidence also suggests that sports participation might improve cognitive function and academic performance [ 19 , 20 , 21 , 22 ]. For instance, Ishihara et al recently reported that sports participation was associated with greater academic performance during a two-year follow-up in adolescents aged 12–13 years, which was mediated by the gains in cardiorespiratory fitness [ 23 ].…”
Section: Introductionmentioning
confidence: 99%